Cell Type-Specific Roles of NF-κB Linking Inflammation and Thrombosis - Mussbacher, Marion; Salzmann, Manuel; Brostjan, Christine; Hoesel, Bastian; Schoergenhofer, Christian; Datler, Hannes; Hohensinner, Philipp; Basílio, José; Petzelbauer, Peter; Assinger, Alice; Schmid, Johannes A. (Frontiers in Immunology, 2019)
The transcription factor NF-κB is a central mediator of inflammation with multiple links to thrombotic processes. In this review, we focus on the role of NF-κB signaling in cell types within the vasculature and the circulation that are involved in thrombo-inflammatory processes. All these cells express NF-κB, with important functions in cellular interactions, cell survival and differentiation, as well as expression of cytokines, chemokines and coagulation factors. Even platelets, as anucleated cells, contain NF-κB and its signaling molecules, which are involved in their activation pathways, as well as feedback circuits. The response of endothelial cells to inflammation and NF-κB activation is characterized by the induction of adhesion molecules promoting binding and transmigration of leukocytes, while simultaneously reducing the non-thrombogenic surface. Paracrine signaling from endothelial cells activates NF-κB in vascular smooth muscle cells and causes a switch to a “synthetic” state associated with a decrease of contractile proteins, which is also involved in cellular transition towards macrophage-like cells. Monocytes react to an inflammatory situation with enforced expression of tissue factor and after differentiation to macrophages with an altered polarization. Neutrophils respond with an extension of their life span – and upon full activation they can expel their DNA thereby forming so-called neutrophil extracellular traps (NETs), which exert antibacterial functions, but also induce a strong coagulatory response. This may cause the formation of clinically unnoticed microthrombi that are important for the immobilization of pathogens, a process designated as immunothrombosis. However, deregulation of the complex cellular links between inflammation and thrombosis by unrestrained NET formation or the loss of the endothelial layer due to mechanical rupture or erosion can result in rapid activation and aggregation of platelets and the manifestation of a thrombo-inflammatory disease. Sepsis is an important example of such a disorder caused by a dysregulated host response to infection finally leading to severe coagulopathies. NF-κB is critically involved in these pathophysiological processes as it induces both inflammatory and thrombotic responses.